MULTIVARIATE MODELING OF C02 LOADING IN AQUEOUS DEA, MDEA AND THEIR MIXTURES BY USING RAMAN SPECTROSCOPY - SHAHID, MUHAMMAD ZUBAIR (2015)
Since Carbon dioxide (C02) management is a vital issue, CO2 must be removed from the industrial flue gas streams and natural gas. There are several approaches to capture CO2, however chemical absorption in alkanolamines is the most commercially recognized method. Thus, it is meaningful to struggle for the improvement in its process efficiency. This objective can be achieved in one of the ways by replacing the sluggish methods of manual C02 loading measurement with fast, accurate and robust measurement using process analytical method. Therefore, in the present study, the monitoring of C02 loading in alkanolamines (aqueous DEA, MDEA and their mixtures) by using Raman spectroscopy has been proposed. For this purpose, C02 is charged into alkanolamines with various aqueous concentrations (10%, 20% and 30%) over a wide range of C02 loading (0.019-1.322 C02 moles/ amine moles). This process is carried out in a batch absorption cell or reactor. The instantaneous value of C02 loading during its absorption process has been determined by using pressure drop method.